2019
DOI: 10.3389/fneur.2019.00060
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipoprotein Profile Is Associated With Protective Effects of Oral Contraceptive Use on Multiple Sclerosis Severity: A Cross-Sectional Study

Abstract: Background: The mechanisms underlying the influence of sex hormones in multiple sclerosis (MS) are uncertain. Sex steroids interact with cholesterol metabolism and the serum lipid profile has been associated with the severity of the disease. We hypothesized that the putative associations between lipoprotein metabolism and MS could be modulated by sex steroids exposure. The aim of this study was to investigate whether oral contraceptives (OC) use changes the lipoprotein profile associated with disability in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Therefore, any distortion in these biomolecules is likely to give rise to severe problems which may end up with neuron loss. Current findings support the idea of such relation between lipid profile and disease progression 89,95‐99 . As we investigated similar characteristics, data showed considerable difference in terms of high total cholesterol, triglyceride, and LDL‐C levels as well as low HDL‐C level in cases.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, any distortion in these biomolecules is likely to give rise to severe problems which may end up with neuron loss. Current findings support the idea of such relation between lipid profile and disease progression 89,95‐99 . As we investigated similar characteristics, data showed considerable difference in terms of high total cholesterol, triglyceride, and LDL‐C levels as well as low HDL‐C level in cases.…”
Section: Discussionsupporting
confidence: 81%
“…Supporting such an interpretation is that impairments in estrogen- and lipid metabolism have been implicated in the development of and in predicting the severity of schizophrenia ( 3 , 11 , 78 83 ). Further support of an estrogen-cholesterol interaction comes from studies of other neurological conditions with a similar sex bias and abnormal cholesterol metabolism, such as Alzheimer's disease ( 84 ) and multiple sclerosis ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is an essential molecule to maintain the homeostasis of bones and minerals, and it also has immune regulation functions in the human body. Many studies have shown that vitamin D deficiency is associated with various autoimmune and allergic diseases, such as multiple sclerosis and CU [75,76]. The availability of vitamin D supplements in the treatment of CSU has been confirmed by some small-scale clinical trials [77,78], but the mechanism is still unclear, which may contribute to the pathogenic pathway inhibition of vitamin D-binding protein.…”
Section: Vitamin D3/vitamin D-binding Proteinmentioning
confidence: 99%